Effects of infant bronchiolitis on family life - Assathiany, Rémy; Sznajder, Marc; Cahn-Sellem, Fabienne; Dolard, Claire; Werner, Andreas (Frontiers in Pediatrics, 2024)
Background: Bronchiolitis is a respiratory infection of viral origin and is often linked to syncytial respiratory virus. It is the most frequent cause of hospitalisation in children under 2 years of age and sometimes requires transfer to intensive care. Infectious complications may also arise in the short term, and longer-term progression towards asthma is also possible. The occurrence of bronchiolitis in children may affect families in different ways, and may have psychological, organisational, employment-related, and possibly financial consequences. Objective: To determine the familial and socioeconomic repercussions of bronchiolitis in infants. Setting: Parents with a child with bronchiolitis between January 2021 and May 2022, who were registered at the site of the Association Française de Pédiatrie Ambulatoire (Mpedia site) or at the site of the Malin Programme, which serves families experiencing financial difficulties. Participants: All parents consenting to participate in the study. Results: A total of 2059 valid questionnaires were retrieved, 1318 (64%) obtained from parents through the Mpedia website and 741 (36%) obtained through the Malin Programme. Parents associated with the Malin Programme had more children, as well as higher rates of unemployment and financial difficulties, and required greater medical assistance. Hospitalisation was necessary in 37% of cases and was comparable between groups. During the illness, moderate to severe anxiety was present in 73% of parents; this percentage rose to 87% if the child required hospitalisation. Many parents reported effects on daily home (84%) and work life (90%), and 60% had taken a leave of absence from work. Conclusion: Beyond the immediate or longer-term medical consequences of bronchiolitis in infants, the illness affects families in multiple ways and can lead to anxiety, as well as changes in day-to-day home and work life. Physicians should have greater awareness of these consequences and should strive to decrease their impact.